ASSESSMENT OF THE NUTRITIONAL VALUE OF FADOGIA TRIPHYLLA HERBAL TEA OF ZAMBIA - Juliani, H R.; Koroch, A.; Fonseca, Y.; Malumo, H.; Diawuo, B.; Simon, J. E (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Fadogia triphylla, a perennial shrub that can reach up to 120 cm is used both as a local herbal tea and in traditional medicine. Traditional healers have reported the use of Fadogia spp. in the treatment of coughs, ascariasis, abdominal pains and stomachs. There is limited information about the nutritional and medicinal value of the leaves of this local tea. Thus, the objective in this study was to asses the nutritional value and herbal tea characteristics of F. triphylla leaves from Zambia. Fadogia triphylla leaves were collected from Shatumbu district, Lusaka at two different times (June 2006 and August 2006). The dry Fadogia leaves were then subjected to foreign matter analysis and moisture content analysis. Total ashes and total insoluble ashes, total phenols, antioxidant activity, and elemental and caffeine. The leaves are high in antioxidant components (8%) and rich in minerals (7%), potassium (1%), calcium (1.3-1.8%) and manganese (90-71 mg/100 g). No caffeine was detected in the leaves based upon HPLC analysis and pure caffeine as the standard, permitting the labelling of this bush tea to be caffeine-free infusion. Initial quality standards were developed for the first time to define quality in Fadogia tea. While a preliminary study, we found the leaves to be high in antioxidant components, rich in minerals (e.g. potassium, calcium and manganese), caffeine-free and the herbal tea to have a pleasant taste. Fadogia leaves contain interesting functional properties that show the leaves to be healthy and nutritional and which may assist in the commercialization of this indigenous tea into non-local markets.